Transcriptomic Insights Into the Growth Phase- and Sugar-Associated Changes in the Exopolysaccharide Production of a High EPS-Producing Streptococcus thermophilus ASCC 1275 - Padmanabhan, Aparna; Tong, Ying; Wu, Qinglong; Zhang, Jiangwen; Shah, Nagendra P. (Frontiers in Microbiology, 2018)
In a previous study, incorporation of high exopolysaccharides (EPS) producing dairy starter bacterium Streptococcus thermophilus ASCC 1275 was found to improve the functionality of low-fat mozzarella cheese and yogurt. This bacterium in its eps gene cluster has a unique pair of chain length determining genes, eps C- eps D, when compared to other sequenced S. thermophilus strains. Hence, the aim of this study was to understand the regulatory mechanism of EPS production in this bacterium using transcriptomic analysis to provide opportunities to improve the yield of EPS. As sugars are considered as one of the major determinants of EPS production, after preliminary screening, we selected three sugars, glucose, sucrose, and lactose to identify the EPS-producing mechanism of this bacterium in the M17 medium. Complete RNA-seq analysis was performed using Illumina HiSeq 2000 sequencing system on S. thermophilus 1275 grown in three different sugars at two-time points, 5 h (log phase) and 10 h (stationary phase) to recognize the mechanism involved in sugar uptake, UDP-sugar formation, EPS assembly and export of EPS outside the bacterial cell. S. thermophilus 1275 was found to produce a high amount of EPS (~430 mg/L) in sucrose supplemented M17 medium when compared to other two sugars. Differential gene expression analysis revealed the involvement of phosphoenolpyruvate phosphotransferase system (PEP-PTS) for glucose as well as sucrose uptake and lacS gene for lactose uptake. The pathways for the formation of UDP-glucose and UDP-galactose were highly upregulated in all the three sugars. In the presence of sucrose, eps1C1D2C2D were found to be highly expressed which refers to high EPS production. Activation of glycogen synthase gene indicates the involvement of synthase-dependent EPS transport in this bacterium. KEGG pathway and COG functional enrichment analysis were also performed to support the result. This is the first report providing the transcriptomic insights into the EPS production mechanism of a common dairy bacterium, S. thermophilus.